PENINGKATAN KETERAMPILAN BERBICARA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW SISWA KELAS IV SDN 21 LIMO KAUM: Penelitian Tindakan Kelas - Zahra Tiara Putri; Nur Azmi Alwi (STKIP Subang, 2024)
This research is based on the problem of students' low speaking skills at SDN 21 Limo Kaum. The aim of this research is to improve students' speaking skills by using a cooperative type learning model Jigsaw. This research is classroom action research (PTK) which uses qualitative and quantitative approaches. Implemented in two cycles, consisting of Cycle I and Cycle II. In cycle I it was carried out in two meetings and cycle II in one meeting. In each cycle there are four stages, namely planning, implementation, observation and reflection. The subjects of this research were 23 class IV students at SDN 21 Limo Kaum and the object of the research was the students' speaking skills. The results of the research showed that there was an increase in students' speaking skills, before the action was implemented the average speaking skill of class IV students at SDN 21 Limo Kaum was 59. After the action was implemented, namely cycle I, the average speaking skill of students increased to 68.5, which results did not meet the criteria. minimum completeness, then cycle II actions are carried out. In cycle II students' speaking skills increased to 77.6. Based on these results it can be concluded that with the cooperative learning model type Jigsaw can improve the speaking skills of class IV students at SDN 21 Limo Kaum.